Effect of Structural and Phase Changes under Relativistic Electron Pulsed Beam Irradiation on the Aluminum Alloys Micro-hardness - Bryukhovetsky, V.V.; Lytvynenko, V.V.; Myla, D.E.; Bychko, V.A.; Lonin, Yu.F.; Ponomarev, A.G.; Uvarov, V.T. (Physics and Chemistry of Solid State, 2021)
The paper studies the distinctive features of micro-hardness value changes in the zone of industrial aluminum alloy 1933 and alloy 1380 irradiated by the relativistic electron beam. The surface layer was modified under the relativistic electron beam injected along with the equal energy parameters. However, we have to claim that some physical and technological properties of the irradiated alloys layer came with some differences. The modified layer micro-hardness increased over 30% in 1933 aluminum alloy and decreased by 10% in 1380 aluminum alloy. The mechanisms affecting the metal material strengthening transformation after a pulsed electron beam application are analyzed. Thus it was established that one of the core impacts to increase the micro-hardness of 1933 aluminum alloy surface layer was fine MgO impurities being absent in the initial alloy and caused by the irradiation, whilst the micro-hardness of the irradiated layer of the 1380 aluminum alloy decreases due to the dissolution during irradiation of the strengthening phases, which were identified in the initial state.